Arab Women as Voiceless Entities in Arab Women Literature: A Study of Al-Shaykh’s The Story of Zahra - Sarhan, Mansour (International Journal of Language and Literary Studies, 2021)
This paper aims to shed light on the miserableness, ill-being, and sufferings of the Arab women in the Arab man-dominated communities as represented in Al-Shaykh’s The Story of Zahra. It aims to expose the Arab men’s view of the Arab women who are perceived not as equal partners but as objects of physical pleasure created to fulfill their sexual desires. The main argument in this paper is meant to unveil the gruesome face of the Arab’s view about their women. It argues that for the Arab women to lead a normal life full of love, peace, respect, and tolerance like their counterparts all over the world, they have to get rid of their inner chains and some social man-made taboos have to be questioned and challenged. This is the basic assumption of this paper. For women be seen as independent and visible entities, their needs must be met and their voices must be heard and both women and men should collaborate to achieve a reformed nationalism free of male dominance. Instead of being viewed as passive victims of male-dominated societies, Arab women must be treated as unique persons with all of their complexities. Besides, the author criticizes the Arab society for the meaning and practice of social discrimination and inequality against women not only in the whole community but also within the same family (male and female).